DYNAMICS OF PUBLIC ADMINISTRATION SYSTEMS: A COMPARATIVE STUDY BETWEEN INDONESIA AND MALAYSIA IN THE ERA OF BUREAUCRATIC REFORM - Hudori, Asma Nadia (International Journal of Multidisciplinary Reseach, 2026)
Public administration reforms have become a strategic agenda for many countries in response to growing demands for effective governance, accountability, and quality public services. Indonesia and Malaysia, as neighboring Southeast Asian countries with shared historical and cultural backgrounds, have implemented different models of public administration reform shaped by their political systems and institutional arrangements. This study aims to comparatively analyze the dynamics of public administration systems in Indonesia and Malaysia during the era of bureaucratic reform, with particular attention to bureaucratic structure, systems of government, administrative reform initiatives, and their implications for public service delivery. This research employs a qualitative approach using a library research method, drawing on classical public administration theories, international academic journals, and official government documents. The findings reveal that Indonesia emphasizes decentralization and participatory governance as key reform strategies, while Malaysia prioritizes centralized coordination, bureaucratic professionalism, and administrative efficiency. These differences significantly influence administrative performance and service delivery outcomes. This study contributes to comparative public administration literature by offering contextual policy lessons for strengthening bureaucratic reform in developing countries. The dindings indicate that Indonesia emphasizes decentralization, democratization, and participatory governance as core elements of its bureaucratic reform agenda. While this approach encourages local innovation and citizen involvement, it also creates challenges related to coordination, capacity disparities, and service quality inconsistency across regions. Malaysia, on the other hand, prioritizes centralized coordination, bureaucratic professionalism, performance-based management, and digital governance. These strategies contribute to relatively uniform service standards and administrative efficiency, although they may limit local participation and flexibility. This study contributes to the literature on comparative public administration by providing contextual insights into bureaucratic reform in Southeast Asia and offering policy recommendations for strengthening governance and public service delivery in developing countries.